2021
DOI: 10.3389/fped.2021.664052
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Plasma Ghrelin Concentrations in Pediatric Sepsis-Associated Acute Respiratory Distress Syndrome: A Single-Center Cohort Study

Abstract: Background: Ghrelin is the endogenous ligand of growth hormone secretagogue receptor 1a, which plays a role in regulating immunity and inflammation. The aim of this study is to assess the diagnostic value of plasma ghrelin in sepsis-associated pediatric acute respiratory distress syndrome (PARDS).Methods: We recruited patients who were admitted to the pediatric ICU (PICU) of the Children's Hospital of Chongqing Medical University between January 2019 and January 2020 and met the diagnostic criteria for sepsis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Indeed, in our population, we found a significant association between CRP and ghrelin. Proinflammatory mediators have been directly associated with ghrelin in pediatric critical illness, and patients with early sepsis—a well‐defined proinflammatory state—reported having high ghrelin levels 30,31 . Although our study is likely underpowered to identify multiple association with inflammatory mediators, we did find CRP to have a significant association with ghrelin even after correction for age and severity of illness.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Indeed, in our population, we found a significant association between CRP and ghrelin. Proinflammatory mediators have been directly associated with ghrelin in pediatric critical illness, and patients with early sepsis—a well‐defined proinflammatory state—reported having high ghrelin levels 30,31 . Although our study is likely underpowered to identify multiple association with inflammatory mediators, we did find CRP to have a significant association with ghrelin even after correction for age and severity of illness.…”
Section: Discussionmentioning
confidence: 59%
“…Proinflammatory mediators have been directly associated with ghrelin in pediatric critical illness, and patients with early sepsis-a well-defined proinflammatory state-reported having high ghrelin levels. 30,31 Although our study is likely underpowered to identify multiple association with inflammatory mediators, we did find CRP to have a significant association with ghrelin even after correction for age and severity of illness. Others have also reported associations with other inflammatory mediators, such as IL-6 and TNF-α (although not corrected for age).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Interestingly, children in this cohort with a history of hematopoietic cellular transplantation (HCT) had higher levels of IL-8, IL-18, IL-10, and TNFR2 (108). A small single-site study indicated that ghrelin, a peptide the regulates immunity, is elevated in children with sepsis-associated PARDS (142).…”
Section: Resultsmentioning
confidence: 99%